PENGARUH PERPUTARAN AKTIVA TETAP, HUTANG JANGKA PANJANG, DAN MODAL KERJA TERHADAP RETURN ON INVESTMENT - Ubaidillah Dzaki Nabhan; Bambang Tutuko; Herwin Kurniawan (Universitas Jember, 2020)
This study aims to find out how the relationship between fixed assets turnover, long term debt, and working capital to Return on Investment (ROI). The sample in this study was 35 data consisting of five transportation companies on the Indonesia Stock Exchange (IDX) from 2012-2018 using the purpose sampling method. Analysis of regression results was carried out after the model did not experience the symptoms of classical assumptions such as multicollinearity, autocorrelation, and heteroscedasticity. The research was processed using IBM SPSS Statistic software, 25,0. Based on the results of the study show that the fixed assets turnover partial shows a positive and significant value of the ROI with a value of tcount (10,699) > ttable (2,0395) and significance of 0,00 < 0,025. The next result shows that the partial long term debt negative and significant of the ROI with a value of tcount (-2,535) > -ttable (-2,0395) and significance of 0,016 < 0,025. Whereas, partially, significant working capital of the ROI positive and significant value with tcount (2,228) > ttable (2,0395) with a significance of 0,023 < 0,025. Simultaneously have a positive and significant effect of the ROI with Fcount (49,219) > Ftable (2,91) with a significant level of 0,000 <0,05. Keywords: Fixed Assets Turnover, Long Term Debt, Working Capital, Return on Investment